The translocation of negatively charged residues across the membrane is driven by the electrochemical potential: evidence for an electrophoresis-like membrane transfer mechanism. - Cao, G (1995)
The role of the membrane electrochemical potential in the translocation of acidic and basic residues across the membrane was investigated with the M13 procoat protein, which has a short periplasmic loop, and leader peptidase, which has an extended periplasmically located N-terminal tail. For both proteins we find that the membrane potential promotes membrane transfer only when negatively charged residues are present within the translocated domain. When these residues are substituted by uncharged amino acids, the proteins insert into the membrane independently of the potential. In contrast, when a positively charged residue is present within the N-terminal tail of leader peptidase, the potential impedes translocation of the tail domain. However, an impediment was not observed in the case of the procoat protein, where positively charged residues in the central loop are translocated even in the presence of the membrane potential. Intriguingly, several of the negatively charged procoat proteins required the SecA and SecY proteins for optimal translocation. The studies reported here provide insights into the role of the potential in membrane protein assembly and suggest that electrophoresis can play an important role in controlling membrane topology.